The permeability of fontainebleau sandstone to gases and liquids. (2nd May 2016) - Chen, Meng; Li, Min; Wang, Ying; Zhao, Jin-Zhou; Xiao, Wen-Lian
ABSTRACT: Klinkenberg-corrected gas permeability ( k∞ ) and liquid permeability ( kl ) are usually considered equal and used to describe the intrinsic permeability of reservoirs. In this study, permeabilities of 30 outcrop Fontainebleau sandstones were measured using nitrogen gas and distilled water at room temperature. As a result, k∞ was times larger than kl, presence of liquid-matrix coupling and thin water films were considered to be the primary reasons. A universal permeability model based on percolation network model was introduced and the simulated permeability was obtained to compare kl and k∞, which indicated that k∞ was more suitable for characterizing the intrinsic permeability.